Avaliação dos dados SRTM através de análise altimétrica e morfométrica de bacias hidrográficas no Semi-Árido - Costa, Carlos Alexandre Gomes (2008)
Face to global climate change it is necessary a better understanding of the hydrological and environmental dynamics. To characterize them in a short time with reliability is an important requirement for the science. Topography is a major factor to understand these factors. Its determination is onerous, both economically and temporally, and the dynamics of environmental transformations that alters its pattern must be considered. In the year 2000, through a interferometric RADAR topographic mission (SRTM) led by NASA in cooperation with the German (DRL) and the Italian (ASI) space agencies, a Digital Elevation Model was generated by the employment of RADAR interferometry. These data are available costless and have been greatly used by scientists. Nonetheless, since it is a RADAR interferometer product, it represents the Earth surface and is subjected to the influence of vegetation, what may make this DEM unriliable in works that require a high detail level and good precision. Therefore, the objective of this research is to validate SRTM data to the Brazilian semi-arid conditions and, based on these data, characterize the physiograph of watersheds in the Jaguaribe basin. The methodology used in the SRTM data validation consists in a comparison and statistical analysis of field data obtained with a differential GPS (DGPS) and other data bases such as the DSG/SUDENE maps and level reference points from IBGE in the Jaguaribe basin located in Ceará State. Results present an elevation error of approximately 7 m in relation to the level reference points in the basin. For the use of DGPS on a plan relief with very low slopes and vegetation with low heights, results show an elevation error of approximately 1.7 m. Vegetation cover influenced the variation in SRTM data to vegetation with higher mean height. To the physiographic characterization, values not larger than 50 pixels must be adopted as the contributing area of SRTM (90m), used in the generation of the river network and the Hydrological Consistent Digital Elevation Model (HCDEM) in the study area. To areas with low slopes, the threshold value must be reviewed. The development of a reference bibliography with physiographic characterization associated to the use of a Geographic Information System (GIS) and a DEM is fundamental as it enhances the possibilities of generating products from remote sensing and geo-processing techniques. The use of ArcHydro extension facilitates a physiographic characterization and allows the storage and use of these data as a GIS.